Pengaruh Etika Bisnis Islam terhadap Keberhasilan Usaha Pedagang Wisata Kuliner di Wanayasa Kuliner Fair - Muhamad Tedy Restu Putra; Arief Mulyawan Thoriq; Hamdan Ardiansyah (Masoem University, 2023)
In practice, there are several Wanayasa Culinary Fair traders who do not apply good Islamic business ethics. This can have an impact on the success of the trader's business at the Wanayasa culinary fair. Because with good Islamic business ethics can provide opportunities for greater business success. This study aims to determine the correlational relationship between Islamic business ethics variables and business success variables. This study used a quantitative correlation method with a saturated sampling technique with a total population of 50 traders. The analysis technique used in this research is statistical analysis technique. Based on the results of data analysis, showed the results of a simple linear regression test with a significant value of 0.003. This value interprets that there is a significant relationship between Islamic business ethics variables and business success variables. The direction of influence shown is a positive direction of influence, which means that the higher the Islamic business ethics, the higher the success of the trader's business. The contribution made by Islamic business ethics to business success is 17.3%. This contribution shows that Islamic business ethics has an effect of 17.3% on the success of traders' businesses at the Wanayasa Culinary Fair.